Antibiotics from predatory bacteria - Korp, Juliane; Vela Gurovic, María S.; Nett, Markus (Beilstein Journal of Organic Chemistry, 2016)
Bacteria, which prey on other microorganisms, are commonly found in the environment. While some of these organisms act as solitary hunters, others band together in large consortia before they attack their prey. Anecdotal reports suggest that bacteria practicing such a wolfpack strategy utilize antibiotics as predatory weapons. Consistent with this hypothesis, genome sequencing revealed that these micropredators possess impressive capacities for natural product biosynthesis. Here, we will present the results from recent chemical investigations of this bacterial group, compare the biosynthetic potential with that of non-predatory bacteria and discuss the link between predation and secondary metabolism.
Keywords: antibiotics; genome mining; Herpetosiphon; myxobacteria; predation

(untitled) - Matz, C.; Kjelleberg, S. (Trends Microbiol., 2005)

(untitled) - Pernthaler, J. (Nat. Rev. Microbiol., 2005)

(untitled) - Chesson, P. (Annu. Rev. Ecol. Syst., 2000)

(untitled) - Jousset, A. (Environ. Microbiol., 2012)

(untitled) - Rønn, R.; Vestergård, M.; Ekelund, F. (Acta Protozool., 2012)

(untitled) - Jurkevitch, E. (Microbe, 2007)

(untitled) - Davidov, Y.; Jurkevitch, E. (BioEssays, 2009)

(untitled) - Guerrero, R.; Esteve, I.; Pedrós-Alió, C.; Gaju, N. (Ann. N. Y. Acad. Sci., 1987)

(untitled) - Bengtson, S. (Paleontol. Soc. Pap., 2002)

(untitled) - Casida, L. E. (Appl. Environ. Microbiol., 1983)

(untitled) - Quinn, G. R.; Skerman, V. B. D. (Curr. Microbiol., 1980)

(untitled) - Kiss, H.; Nett, M.; Domin, N.; Martin, K.; Maresca, J. A.; Copeland, A.; Lapidus, A.; Lucas, S.; Berry, K. W.; Del Rio, T. G.; Dalin, E.; Tice, H.; et al. (Stand. Genomic Sci., 2011)

(untitled) - Sockett, R. E. (Annu. Rev. Microbiol., 2009)

(untitled) - Morgan, A. D.; MacLean, R. C.; Hillesland, K. L.; Velicer, G. J. (Appl. Environ. Microbiol., 2010)

(untitled) - Casida, L. E., Jr (Int. J. Syst. Bacteriol., 1982)

(untitled) - Makkar, N. S.; Casida, L. E. (Int. J. Syst. Evol. Microbiol., 1987)

(untitled) - Seccareccia, I.; Kost, C.; Nett, M. (Appl. Environ. Microbiol., 2015)

(untitled) - Lewin, R. A. (Microb. Ecol., 1997)

(untitled) - Banning, E. C.; Casciotti, K. L.; Kujawinski, E. B. (FEMS Microbiol. Ecol., 2010)

(untitled) - Soo, R. M.; Woodcroft, B. J.; Parks, D. H.; Tyson, G. W.; Hugenholtz, P. (PeerJ, 2015)

(untitled) - Casida, L. E., Jr (Microb. Ecol., 1988)

(untitled) - Martin, M. O. (J. Mol. Microbiol. Biotechnol., 2002)

(untitled) - Esteve, I.; Guerrero, R.; Montesinos, E.; Abellà, C. (Microb. Ecol., 1983)

(untitled) - Guerrero, R.; Pedrós-Alió, C.; Esteve, I.; Mas, J.; Chase, D.; Margulis, L. (Proc. Natl. Acad. Sci. U. S. A., 1986)

(untitled) - Moulder, J. W. (Microbiol. Rev., 1985)

(untitled) - Sockett, R. E.; Lambert, C. (Nat. Rev. Microbiol., 2004)

(untitled) - Berleman, J. E.; Kirby, J. R. (FEMS Microbiol. Rev., 2009)

(untitled) - Cao, P.; Dey, A.; Vassallo, C. N.; Wall, D. (J. Mol. Biol., 2015)

(untitled) - Mendes-Soares, H.; Velicer, G. J. (Microb. Ecol., 2013)

(untitled) - Bode, H. B., Jr; Müller, R. (Angew. Chem., Int. Ed., 2005)

(untitled) - Nett, M.; König, G. M. (Nat. Prod. Rep., 2007)

(untitled) - Müller, R.; Wink, J. (Int. J. Med. Microbiol., 2014)

(untitled) - Schäberle, T. F.; Lohr, F.; Schmitz, A.; König, G. M. (Nat. Prod. Rep., 2014)

(untitled) - Hayward, A. C.; Fegan, N.; Fegan, M.; Stirling, G. R. (J. Appl. Microbiol., 2010)

(untitled) - Xie, Y.; Wright, S.; Shen, Y.; Du, L. (Nat. Prod. Rep., 2012)

(untitled) - Reichenbach, H.; Höfle, G. (Biotechnol. Adv., 1993)

(untitled) - de Bruijn, I.; Cheng, X.; de Jager, V.; Gómez Expósito, R.; Watrous, J.; Patel, N.; Postma, J.; Dorrestein, P. C.; Kobayashi, D.; Raaijmakers, J. M. (BMC Genomics, 2015)

(untitled) - König, G. M.; Dávila-Céspedes, A.; Hufendiek, P.; Crüsemann, M.; Schäberle, T. F. (Beilstein J. Org. Chem., 2016)

(untitled) - Kaiser, D.; Robinson, M.; Kroos, L. (Cold Spring Harbor Perspect. Biol., 2010)

(untitled) - Claessen, D.; Rozen, D. E.; Kuipers, O. P.; Søgaard-Andersen, L.; van Wezel, G. P. (Nat. Rev. Microbiol., 2014)

(untitled) - Nan, B.; Zusman, D. R. (Annu. Rev. Genet., 2011)

(untitled) - Li, Z.-F.; Li, X.; Liu, H.; Liu, X.; Han, K.; Wu, Z.-H.; Hu, W.; Li, F.-F.; Li, Y.-Z. (J. Bacteriol., 2011)

(untitled) - Goldman, B. S.; Nierman, W. C.; Kaiser, D.; Slater, S. C.; Durkin, A. S.; Eisen, J. A.; Ronning, C. M.; Barbazuk, W. B.; Blanchard, M.; Field, C.; Halling, C.; Hinkle, G.; et al. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Huntley, S.; Zhang, Y.; Treuner-Lange, A.; Kneip, S.; Sensen, C. W.; Søgaard-Andersen, L. (J. Bacteriol., 2012)

(untitled) - Huntley, S.; Kneip, S.; Treuner-Lange, A.; Søgaard-Andersen, L. (Genome Announc., 2013)

(untitled) - Schneiker, S.; Perlova, O.; Kaiser, O.; Gerth, K.; Alici, A.; Altmeyer, M. O.; Bartels, D.; Bekel, T.; Beyer, S.; Bode, E.; Bode, H. B.; Bolten, C. J.; et al. (Nat. Biotechnol., 2007)

(untitled) - Han, K.; Li, Z.-F.; Peng, R.; Zhu, L.-P.; Zhou, T.; Wang, L.-G.; Li, S.-G.; Zhang, X.-B.; Hu, W.; Wu, Z.-H.; Qin, N.; Li, Y.-Z. (Sci. Rep., 2013)

(untitled) - Blattner, F. R.; Plunkett, G., III; Bloch, C. A.; Perna, N. T.; Burland, V.; Riley, M.; Collado-Vides, J.; Glasner, J. D.; Rode, C. K.; Mayhew, G. F.; Gregor, J.; Davis, N. W.; et al. (Science, 1997)

(untitled) - Huntley, S.; Hamann, N.; Wegener-Feldbrügge, S.; Treuner-Lange, S.; Kube, M.; Reinhardt, R.; Klages, S.; Müller, R.; Ronning, C. M.; Nierman, W. C.; Søgaard-Andersen, L. (Mol. Biol. Evol., 2011)

(untitled) - Chen, X.-J.; Han, K.; Feng, J.; Zhuo, L.; Li, Y.-J.; Li, Y.-Z. (Stand. Genomic Sci., 2016)

(untitled) - Weber, T.; Blin, K.; Duddela, S.; Krug, D.; Kim, H. U.; Bruccoleri, R.; Lee, S. Y.; Fischbach, M. A.; Müller, R.; Wohlleben, W.; Breitling, R.; Takano, E.; et al. (Nucleic Acids Res., 2015)

The Prokaryotes - Garcia, R.; Müller, R. (The Family Polyangiaceae, 2014)

(untitled) - Garcia, R.; Gerth, K.; Stadler, M.; Dogma, I. J., Jr; Müller, R. (Mol. Phylogenet. Evol., 2010)

(untitled) - Garcia, R.; Pistorius, D.; Stadler, M.; Müller, R. (J. Bacteriol., 2011)

(untitled) - Berleman, J. E.; Chumley, T.; Cheung, P.; Kirby, J. R. (J. Bacteriol., 2006)

(untitled) - Wenzel, S. C.; Müller, R. (Nat. Prod. Rep., 2009)

(untitled) - Cortina, N. S.; Krug, D.; Plaza, A.; Revermann, O.; Müller, R. (Angew. Chem., Int. Ed., 2012)

(untitled) - Kunze, B.; Bedorf, N.; Kohl, W.; Höfle, G.; Reichenbach, H. (J. Antibiot., 1989)

(untitled) - Silakowski, B.; Kunze, B.; Nordsiek, G.; Blöcker, H.; Höfle, G.; Müller, R. (Eur. J. Biochem., 2000)

(untitled) - Schieferdecker, S.; König, S.; Koeberle, A.; Dahse, H.-M.; Werz, O.; Nett, M. (J. Nat. Prod., 2015)

(untitled) - Wenzel, S. C.; Meiser, P.; Binz, T. M.; Mahmud, T.; Müller, R. (Angew. Chem., Int. Ed., 2006)

(untitled) - Ohlendorf, B.; Kehraus, S.; König, G. M. (J. Nat. Prod., 2008)

(untitled) - Meiser, P.; Bode, H. B.; Müller, R. (Proc. Natl. Acad. Sci. U. S. A., 2006)

(untitled) - Meiser, P.; Weissman, K. J.; Bode, H. B.; Krug, D.; Dickschat, J. S.; Sandmann, A.; Müller, R. (Chem. Biol., 2008)

(untitled) - Krug, D.; Zurek, G.; Revermann, O.; Vos, M.; Velicer, G. J.; Müller, R. (Appl. Environ. Microbiol., 2008)

(untitled) - Trowitzsch-Kienast, W.; Gerth, K.; Wray, V.; Reichenbach, H.; Höfle, G. (Liebigs Ann. Chem., 1993)

(untitled) - Wenzel, S. C.; Kunze, B.; Höfle, G.; Silakowski, B.; Scharfe, M.; Blöcker, H.; Müller, R. (ChemBioChem, 2005)

(untitled) - Miyanaga, S.; Sakurai, H.; Saiki, I.; Onaka, H.; Igarashi, Y. (Bioorg. Med. Chem., 2009)

(untitled) - Korp, J.; König, S.; Schieferdecker, S.; Dahse, H.-M.; König, G. M.; Werz, O.; Nett, M. (ChemBioChem, 2015)

(untitled) - Jansen, R.; Reifenstahl, G.; Gerth, K.; Reichenbach, H.; Höfle, G. (Liebigs Ann. Chem., 1983)

(untitled) - Gerth, K.; Jansen, R.; Reifenstahl, G.; Höfle, G.; Irschik, H.; Kunze, B.; Reichenbach, H.; Thierbach, G. (J. Antibiot., 1983)

(untitled) - Friedrich, T.; Van Heek, P.; Leif, H.; Ohnishi, T.; Forche, E.; Kunze, B.; Jansen, R.; Trowitzsch-Kienast, W.; Höfle, G.; Reichenbach, H.; Weiss, H. (Eur. J. Biochem., 1994)

(untitled) - Bode, H. B.; Meiser, P.; Klefisch, T.; Cortina, N. S. D. J.; Krug, D.; Göhring, A.; Schwär, G.; Mahmud, T.; Elnakady, Y. A.; Müller, R. (ChemBioChem, 2007)

(untitled) - Rosenberg, E.; Vaks, B.; Zuckerberg, A. (Antimicrob. Agents Chemother., 1973)

(untitled) - Gerth, K.; Irschik, H.; Reichenbach, H.; Trowitzsch, W. (J. Antibiot., 1982)

(untitled) - Trowitzsch, W.; Wray, V.; Gerth, K.; Höfle, G. (J. Chem. Soc., Chem. Commun., 1982)

(untitled) - Onishi, N.; Izaki, K.; Takahashi, H. (J. Antibiot., 1984)

(untitled) - Takayama, S.; Yamanaka, S.; Miyashiro, S.; Yokokawa, Y.; Shibai, H. (J. Antibiot., 1988)

(untitled) - Simunovic, V.; Zapp, J.; Rachid, S.; Krug, D.; Meiser, P.; Müller, R. (ChemBioChem, 2006)

(untitled) - Rosenberg, E.; Dworkin, M. (J. Ind. Microbiol., 1996)

(untitled) - Xiao, Y.; Gerth, K.; Müller, R.; Wall, D. (Antimicrob. Agents Chemother., 2012)

(untitled) - Xiao, Y.; Wei, X.; Ebright, R.; Wall, D. (J. Bacteriol., 2011)

(untitled) - Morett, E.; Segovia, L. (J. Bacteriol., 1993)

(untitled) - Volz, C.; Kegler, C.; Müller, R. (Chem. Biol., 2012)

(untitled) - Bretscher, A. P.; Kaiser, D. (J. Bacteriol., 1978)

(untitled) - Weissman, K. J.; Müller, R. (Nat. Prod. Rep., 2010)

(untitled) - Schieferdecker, S.; König, S.; Weigel, C.; Dahse, H.-M.; Werz, O.; Nett, M. (Chem. – Eur. J., 2014)

(untitled) - Zhang, L.; Wang, H.; Fang, X.; Stackebrandt, E.; Ding, Y. (J. Microbiol. Methods, 2003)

(untitled) - Schieferdecker, S.; Exner, T. E.; Gross, H.; Roth, M.; Nett, M. (J. Antibiot., 2014)

(untitled) - Mohr, K. I.; Stechling, M.; Wink, J.; Wilharm, E.; Stadler, M. (MicrobiologyOpen, 2016)

(untitled) - Dawid, W. (FEMS Microbiol. Rev., 2000)

(untitled) - Surup, F.; Viehrig, K.; Mohr, K. I.; Herrmann, J.; Jansen, R.; Müller, R. (Angew. Chem., Int. Ed., 2014)

(untitled) - Hille-Rehfeld, A. (Chem. Unserer Zeit, 2015)

(untitled) - Holzgrabe, U. (Pharmakon, 2015)

(untitled) - Irschik, H.; Gerth, K.; Höfle, G.; Kohl, W.; Reichenbach, H. (J. Antibiot., 1983)

(untitled) - Kohl, W.; Irschik, H.; Reichenbach, H.; Höfle, G. (Liebigs Ann. Chem., 1983)

(untitled) - Irschik, H.; Jansen, R.; Höfle, G.; Gerth, K.; Reichenbach, H. (J. Antibiot., 1985)

(untitled) - Jansen, R.; Höfle, G.; Irschik, H.; Reichenbach, H. (Liebigs Ann. Chem., 1985)

(untitled) - Schäberle, T. F.; Schmitz, A.; Zocher, G.; Schiefer, A.; Kehraus, S.; Neu, E.; Roth, M.; Vassylyev, D. G.; Stehle, T.; Bierbaum, G.; Hoerauf, A.; Pfarr, K.; et al. (J. Nat. Prod., 2015)

(untitled) - Erol, Ö.; Schäberle, T. F.; Schmitz, A.; Rachid, S.; Gurgui, C.; El Omari, M.; Lohr, F.; Kehraus, S.; Piel, J.; Müller, R.; König, G. M. (ChemBioChem, 2010)

(untitled) - Sucipto, H.; Wenzel, S. C.; Müller, R. (ChemBioChem, 2013)

(untitled) - Schäberle, T. F. (Beilstein J. Org. Chem., 2016)

(untitled) - Schäberle, T. F.; Schiefer, A.; Schmitz, A.; König, G. M.; Hoerauf, A.; Pfarr, K. (Int. J. Med. Microbiol., 2014)

(untitled) - Mukhopadhyay, J.; Das, K.; Ismail, S.; Koppstein, D.; Jang, M.; Hudson, B.; Sarafianos, S.; Tuske, S.; Patel, J.; Jansen, R.; Irschik, H.; Arnold, E.; et al. (Cell, 2008)

(untitled) - Srivastava, A.; Talaue, M.; Liu, S.; Degen, D.; Ebright, R. Y.; Sineva, E.; Chakraborty, A.; Druzhinin, S. Y.; Chatterjee, S.; Mukhopadhyay, J.; Ebright, Y. W.; Zozula, A.; et al. (Curr. Opin. Microbiol., 2011)

(untitled) - Cramer, P. (Curr. Opin. Struct. Biol., 2002)

(untitled) - Yamaguchi, H.; Nakayama, Y.; Takeda, K.; Tawara, K.; Maeda, K.; Takeuchi, T.; Umezawa, H. (J. Antibiot., 1957)

(untitled) - Kunze, B.; Reichenbach, H.; Augustiniak, H.; Höfle, G. (J. Antibiot., 1982)

(untitled) - Fujimoto, H.; Kinoshita, T.; Suzuki, H.; Umezawa, H. (J. Antibiot., 1970)

Mechanism of Action of Antimicrobial and Antitumor Agents - Pestka, S. (Althiomycin, 1975)

(untitled) - Cortina, N. S.; Revermann, O.; Krug, D.; Müller, R. (ChemBioChem, 2011)

(untitled) - Gerc, A. J.; Song, L.; Challis, G. L.; Stanley-Wall, N. R.; Coulthurst, S. J. (PLoS One, 2012)

(untitled) - Baumann, S.; Herrmann, J.; Raju, R.; Steinmetz, H.; Mohr, K. I.; Hüttel, S.; Harmrolfs, K.; Stadler, M.; Müller, R. (Angew. Chem., Int. Ed., 2014)

Bergey’s Manual of Systematic Bacteriology - Garrity, G. M.; Holt, J. G.; Castenholtz, R. W.; Pierson, B. K.; Keppen, O. I.; Gorlenko, V. M. (Phylum BVI. Chloroflexi phy. nov, 2001)

(untitled) - Hugenholtz, P.; Stackebrandt, E. (Int. J. Syst. Evol. Microbiol., 2004)

(untitled) - Gupta, R. S.; Chander, P.; George, S. (Antonie van Leeuwenhoek, 2013)

(untitled) - Sutcliffe, I. C. (Trends Microbiol., 2010)

(untitled) - Frigaard, N.-U.; Bryant, D. A. (Arch. Microbiol., 2004)

The Prokaryotes - Lee, N.; Reichenbach, H. (The genus Herpetosiphon, 2006)

(untitled) - Ward, L. M.; Hemp, J.; Pace, L. A.; Fischer, W. W. (Genome Announc., 2015)

(untitled) - Kastner, S.; Müller, S.; Natesan, L.; König, G. M.; Guthke, R.; Nett, M. (Arch. Microbiol., 2012)

(untitled) - Tang, K.-H.; Barry, K.; Chertkov, O.; Dalin, E.; Han, C. S.; Hauser, L. J.; Honchak, B. M.; Karbach, L. E.; Land, M. L.; Lapidus, A.; Larimer, F. W.; Mikhailova, N.; et al. (BMC Genomics, 2011)

(untitled) - Nett, M.; Ikeda, H.; Moore, B. S. (Nat. Prod. Rep., 2009)

(untitled) - Rudolf, J. D.; Yan, X.; Shen, B. (J. Ind. Microbiol. Biotechnol., 2016)

(untitled) - Nett, M.; Erol, Ö.; Kehraus, S.; Köck, M.; Krick, A.; Eguereva, E.; Neu, E.; König, G. M. (Angew. Chem., Int. Ed., 2006)

(untitled) - Zhang, J.; Polishchuk, E. A.; Chen, J.; Ciufolini, M. A. (J. Org. Chem., 2009)

(untitled) - Schieferdecker, S.; Domin, N.; Hoffmeier, C.; Bryant, D. A.; Roth, M.; Nett, M. (Eur. J. Org. Chem., 2015)

(untitled) - Nakano, C.; Oshima, M.; Kurashima, N.; Hoshino, T. (ChemBioChem, 2015)

(untitled) - Pidot, S. J.; Coyne, S.; Kloss, F.; Hertweck, C. (Int. J. Med. Microbiol., 2014)